ANALISIS KONSEP FISIKA PADA TEKNOLOGI IRIGASI TETES DI LAHAN PERTANIAN ARGO EXPO INSTITUT NASIONAL FLORES - Fransiskus Jenga Lena; Tri Maria magdalena Wea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The application of physics concepts in agricultural technology such as in drip irrigation systems shows how important it is to understand the principles of physics in developing agricultural technology. This study aims to analyze the physics concepts of drip irrigation technology in agricultural land. The method used is qualitative description. Data collection in this study utilized direct observation. The research was conducted at the Argo Axpo practice field at the Flores National Institute. Data analysis used qualitative analysis. Research results show that the drip irrigation system applies the principles of physics. Drip irrigation is a method of directly delivering water to plants, either to the root zone or to the soil surface, through continuous, slow drips. Irrigation application is adjusted to the type and water needs of each plant. The application of drip irrigation technology systems involves various fluid physics concepts such as Bernoulli's law, hydrostatic pressure, Pascal's law, capillarity, and gravity. The conclusion of this study is that the application of drip irrigation systems involves various physics concepts such as Bernoulli's law, hydrostatic pressure, Pascal's law, capillarity, and gravity. These principles help regulate water flow to meet plant needs and reduce waste. Drip irrigation is suitable for use in water-limited areas and can support optimal plant growth.